Sorption and emulsion liquid membranes in the remediation of metal processing waste water effluents using rhodium, trioctylamine and trihexylamine as a model - Moyo, Francis (Rhodes University, Faculty of Pharmacy, Pharmacy)
Two optimised ELMs were prepared with the diluent always being 30 % solution of toluene in kerosene. The first ELM contained 30.000 g/L (w/v) polyisobutylene, 10.870 g/L (m/v) of trioctyl amine and 51.001 g/L (m/v) of SPAN 80. The other optimised ELM was composed of 20.000 g/l of polyisobutylene, 10.268 g/l trioctyl amine and 50.024 g/l of SPAN 80. The stripping phase was always 2 M HNO3 and the mixing ratios of organic phase to stripping phase were 1:1 and 2:1. The t-test was used to test for the difference between the mean micro-droplet sizes had a p-value of 0.3018 at 5 % level of significance, i.e. there was no statistically the mean micro-droplet size of the optimised ELMs. Demulsification was performed with polyethylene glycol with molecular weight of 400 g/mol at 50 Â± 1 Â°C for 24 hours. The volumetric ratio of treated side-stream and the ELM was 5:1 and 98.7 to 108 % of the initial Rh amount was recovered in the stripping phase after chemical demulsification. Major carryover of the diluent components into the stripping phase observed was from trioctyl amine, toluene and polyethylene glycol was observed. The final spent side-stream should not be discharged into the environment based on the acute Daphnia pulex toxicity test. For sorption studies, the specific surface area of kaolin was 18.21 0.8 m2 g-1 and loss on ignition was 0.0086 0.004 %. Removal efficiencies of trioctyl amine for 10 g of kaolin and particle size 65-100 Î¼m and 101-400 Î¼m were 18.1 % and 17.5 % respectively while sorption capacities were 0.92 g/g and 0.88 g/g respectively. The removal efficiency of 20 g of kaolin was 35.8 % and 33.3 % and sorption capacities were 0.93 g/g and 0.87 g/g respectively. For particle sizes 101-400 Î¼m, the R2 values obtained for Freundlich and Langmuir were 0.9757 and 0.9819 respectively. The n and Kf for Freundlich isotherm were 1.086 and 2.622. Removal efficiency for trihexyl amine for particle size 101-400 Î¼m and 65-100 Î¼m was 28.5 % and 29.3 % respectively while sorption capacities were 0.73 g/g and 0.75 g/g respectively. The R2 values obtained for Freundlich and Langmuir for particle sizes 101-400 Î¼m were 0.957 and 0.989 respectively. The n and Kf for Freundlich isotherm were 1.307 and 2.151 respectively. These results suggest that kaolinite could potentially be used in remediation of metal wastewaters containing hydrophobic extractants.
Keywords: Liquid membranes; Rhodium; Trioctylamine; Trihexylamine; Emulsions (Pharmacy); Sorption